Evidence for an interaction between cannabinoidergic and dopaminergic systems with melanocortin MC3/ MC4 receptors in regulating food intake of neonatal chick - Mohammad Bameri; Morteza Zendedel kheybari; Bita Vazir; Ahmad Asghari; Negar Panahi (The Iranian Journal of Veterinary Science and Technology, 2021)
The current study aimed to see how the central dopaminergic and cannabinoidergic mechanisms affect melanocortin-induced food intake in the neonatal layer chickens. In this regard, 9 experiments were designed. In experiment 1, chicks injected with control solution, MTII (2.5, 5, and 10 ng). In experiment 2, control solution, L-DOPA (125 nmol), MTII (10 ng), and L-DOPA + MTII were applied to the birds. Experiments 3-9 were similar to experiment 2, except birds injected with 6-OHDA (150 nmol), SCH23390 (5 nmol), AMI-193 (5 nmol), NGB2904 (6.4 nmol), L-741,742 (6 nmol), SR141716A (6.25 µg), and AM630 (5 µg) instead of L-DOPA. Then, cumulative food intake was recorded at 30, 60, and 120 min following injection. According to the results, in comparison with the control group, dose-dependent hypophagia was observed in 3-h food-deprived neonatal layer chickens following ICV injection of MTII (2.5, 5, and 10 ng) (P<0.05). ICV injection of L-DOPA and SR141716A increased hypophagia induced by MTII in chickens (P<0.05), while 6-OHDA greatly suppressed MTII- induced hypophagia (P<0.05). In addition, SCH23390 and AMI-193 greatly weakened the MTII-induced hypophagia in neonatal layer chickens (P<0.05). However, NGB2904, L-741742 and AM630 had no role on hypophagia induced by MTII (P>0.05). These results demonstrated that melanocortin-induced hypophagia in the neonatal layer chickens is likely mediated by D1, D2, and CB1 receptors.